Perceptual consensus on cross-country ski-snow performance: a questionnaire study of experts and non-experts - Kalén, A.; Abrahamsson, J.; Kalliorinne, K.; Holmberg, H.-C.; Almqvist, A. (Frontiers in Sports and Active Living, 2026)
Introduction: Understanding how skiers and ski technicians perceive snow conditions and ski preparation is essential for optimising glide performance in cross-country (XC) skiing. While tribological research has established how snow microstructure, water-film formation, and ski-snow interactions influence friction, comparatively little is known about how skiers and ski technicians interpret these mechanisms in practice.